Hotel Transylvania 2 [videorecording (DVD)] (Sony Pictures Home Entertainment, 2016)
Everything seems to be changing for the better at Hotel Transylvania. Dracula's rigid monster-only hotel policy has finally relaxed, opening up its doors to human guests. But behind closed coffins, Drac is worried that his adorable half-human, half-vampire grandson, Dennis, isn't showing signs of being a vampire.